Jane Eyre - Young, Robert; Brenman, Greg; Bronte, Charlotte, 1816-1855; London Weekend Television, ltd.; A & E Home Video; New Video Group (New York : A & E Home Video, 1999)
The story of a plain governess who finds love with the mysterious Mr. Rochester
Based on the book by Charlotte Bronte
Executive producer, Sally Head ; screenplay, Kay Mellor ; music, Richard Harvey
Cast : Samantha Morton, Ciaran Hinds, Gemma Jones, Richard Hawley, Abigail Cruttenden.
Keywords: Bronte, Charlotte, -- 1816-1855; Governesses in literature; Man-woman relationship -- Fiction; Feature films; Love stories